Social skills as factors of protection of the program Spice up your life without drugs or violence in schoolchildren in Huaycán - Mori Sánchez, María Del Pilar (2018)
The present study seeks to identify the results obtained from the application of the Social Skills Component of a social Program “Adereza tu vida sin drogas ni violencia”, in students of the primary level of an area of Huaycán. In order to respond the aims of the study, the qualitative approach, participatory action research design, and an initial and formative evaluation system were used; 42 girls and 41 boys, aged between 9 and 10 years, participated in the study; most of them are at the age of 9; all participants attend the 5th grade of primary school. The main results of the program allow to describe the achievement of indicators of three factors of social skills: Self-esteem, interpersonal relationships and empathy, participatory strategies and implementation methodology allowed to have an efficient, effective and relevant program. Even when the achievement of the indicators has been significant, it is suggested to complement the intervention tasks with parents in order to ensure the sustainability.